Methods of payment, direct takeovers and privately-held targets: evidence of bidder's return on takeovers - Fauzias Mat Nor; Razali Ismail (Penerbit Universiti Kebangsaan Malaysia, 2006)
This study examines whether the proposed acquisition announcement on methods of payment has an impact on the bidder's returns behaviour. The analysIs uses the event study technique. the naive model. a model that is based on the market model with constrained a = 0 and f3 = 1 to compute the abnormal returns and to evaluate the effects of the proposed acquisition announcement on the bidder's returns. The study finds that Malaysian investors appear to he not in favour of cash-based acquisition to be done directly by the bidding company as shown by the significant negative results on the bidder's average residuals after the announcement date. The same goes for acquisition that targets private limited company. The insignificant results obtained on the announcement dale itself may give an Indication that such announcements do not really bring "surprisingly good news" to investors. However, the significant positive results of the bidder's average reSidual on acquisition by equity on and after the announcement. either to be done directly or on private limited takeover, may give an implication that the use of equity conveys favourable information about the bidding firms and are value relevant.